(E)-1-(Anthracen-9-yl)-3-(2-chloro-6-fluorophenyl)- prop-2-en-1-one: crystal structure and Hirshfeld surface analysis - Abdullah, Amzar Ahlami; Hassan, Nur Hafiq Hanif; Arshad, Suhana; Che Khalib, Nuridayanti; Razak, Ibrahim Abdul (International Union of Crystallography, 2016)
In the title compound, C23H14ClFO, the enone moiety adopts an E conformation. The dihedral angle between the benzene and anthracene ring is 63.42 (8) and an intramolecular C—HF hydrogen bond generates an S(6) ring motif. In the crystal, molecules are arranged into centrosymmetric dimers via pairs of C—HF hydrogen bonds. The crystal structure also features C—H and – interactions. Hirshfeld surface analysis was used to confirm the existence of intermolecular interactions.